Application Of Hallimond Tube For The Flotability Study Of Pure Scheelite - Zamri, Nur Hazwani (Universiti Sains Malaysia, 2022)
Scheelite one of the sources for occurrence of tungsten, commonly coexists best in ore deposits with other gangue minerals such as calcite that have the same active Ca-atoms. The study of flotation was carried out via Hallimond Tube to separate scheelite from calcite. This project was implemented to investigate the floatability of pure scheelite via application of Hallimond Tube and to determine the effectiveness different types of collectors on mineral scheelite and other parameters to recover the scheelite. The mineral characterization process involved techniques such as polarised microscope, XRF and XRD. Type of collected that had been used were a mixture collector (oleic acid and naphthenic acid) and oleic acid collector. Next, the percentage recovery of scheelite were compared between both collectors. Based on the experiment’s result, percentage recovery of pure scheelite was discovered higher than 45%. in the conditioning time of 3 minutes for both collectors. At pH value of 9, the percentage recovery for oleic acid collector and mixture collector was the highest which were 50.72% and 52.40%. The percentage of recovery when using mixture collector as 44.98% while the percentage recovery of scheelite when using oleic acid only was 37.46% at two minutes of flotation. As the conclusion, the optimum parameter were three minutes for conditioning time, 2 minutes for flotation time and has pH value of 9. The recovery of pure scheelite was higher when using mixture collector compared to oleic acid collector only.